Detección de Helicobacter Pylori en el Sistema Digestivo por Biopsia en personas que acuden a realizarse Endoscopias en el Hospital Manuel Ygnacio Monteros Valdivieso de Loja. - Viteri Mendoza, Jeniffer Dayanna (2013)
Helicobacter pylori has coexisted with humans for thousands of years, becoming a health problem globally is estimated that approximately 60% of the population is affected. In developing countries, 70 to 90% of the population is infected, with similar prevalence in both men and women, the bacteria interacting with various gastric disorders such as ulcers, gastritis and cancer. Urease test is used for the diagnosis of H. pylori, which has the advantage of providing fast and reliable results after performing an endoscopy. For this reason the study was conducted on Detection of Helicobacter pylori in the digestive system by biopsy in people attending endoscopies performed in the Hospital Manuel Valdivieso Loja Ygnacio Monteros, in order to make the detection of Helicobacter pylori by urease test in gastric tissue biopsy and compare the results with Giemsa stain made ​​by the pathology laboratory. The study is a descriptive, prospective, cross, whose sample is 75 patients attending the endoscopy center Monteros Hospital Valdivieso Manuel Ygnacio Loja, concluding that of the 75 patients: in 68% (51) was detected Helicobacter pylori applying urease test-Line Testing and comparing with the results of Giemsa stain was obtained false positive and false negative, concluding that the test-line Testing is a great contribution for the detection of Helicobacter pylori. Key words: Test of urease, Helicobacter pylori, sensitivity, specificity.